2022
DOI: 10.3389/fevo.2022.894616
|View full text |Cite
|
Sign up to set email alerts
|

Range Size and Niche Breadth as Predictors of Climate-Induced Habitat Change in Epipactis (Orchidaceae)

Abstract: While there is mounting evidence that ongoing changes in the climate system are shifting species ranges poleward and to higher altitudes, responses to climate change vary considerably between species. In general, it can be expected that species responses to climate change largely depend on how broad their ecological niches are, but evidence is still scant. In this study, we investigated the effects of predicted future climate change on the availability of suitable habitat for 14 Epipactis (Orchidaceae) species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The same scheme of poleward range shift as a response to the global warming was already predicted to occur in other plant 87 and animal 88 , 89 species. Evans and Jacquemyn 90 suggested that terrestrial Orchidaceae with a wide distribution will be more capable of shifting their distributions under global warming than species with a restricted geographical range. While obviously species with broader environmental tolerance have higher survival chances than more specialized taxa, the fragility of ecological interactions can further affect persistence of widely distributed organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same scheme of poleward range shift as a response to the global warming was already predicted to occur in other plant 87 and animal 88 , 89 species. Evans and Jacquemyn 90 suggested that terrestrial Orchidaceae with a wide distribution will be more capable of shifting their distributions under global warming than species with a restricted geographical range. While obviously species with broader environmental tolerance have higher survival chances than more specialized taxa, the fragility of ecological interactions can further affect persistence of widely distributed organisms.…”
Section: Discussionmentioning
confidence: 99%
“…While obviously species with broader environmental tolerance have higher survival chances than more specialized taxa, the fragility of ecological interactions can further affect persistence of widely distributed organisms. Studies on future distribution of European orchids are rather scarce and while some taxa ( Nigritella nigra 91 , Pseudorchis albida 92 ) are predicted to lose their suitable niches across their ranges, others are expected to experience a poleward range shift (some Orchis 93 , Ophrys insectifera 94 , some Epipactis 90 ). Noteworthy, none of the previous research considered the importance of mycorrhizal fungi on Orchidaceae distribution and most of the published analyses ignored also the future availability of orchid pollen vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Range expansion could be attributed to the large geographic ranges of most studied species, including E. edulis . Plants with a large geographic range are capable of thriving in varying climatic conditions, which could make them less susceptible to climate change (e.g., Beltrán et al, 2014; Evans & Jacquemyn, 2022). However, when changes in vegetation cover were considered (a more realistic model), we predicted a negative impact for most species, including E. edulis .…”
Section: Discussionmentioning
confidence: 99%
“…The result indicates that species with a very restricted distribution should suffer a low proportion of losses in their current distribution areas, while widespread species should suffer the highest proportion of losses. This seems contradictory at first glance, as species with restricted ranges are expected to lose more area than widely distributed ones, due to the expectation that restricted ranges result from narrower niches (Slatyer et al, 2013;Saupe et al, 2015;Evans and Jacquemyn, 2022). A possible explanation for the lower proportion of loss for species with very restricted ranges may be related to the extreme specialization that can lead some species to "escape" the full impacts of climate change (Foden et al, 2013).…”
Section: Discussionmentioning
confidence: 99%